Mistress [compact disc, unabridged] - Patterson, James, 1947- (Hachette Audio, 2013)
Ben isn't like most people. Unable to control his thoughts, he's a man consumed by his obsessions, cars, tennis, marathons, trains, yachts, and Diana Hotchkiss, a beautiful woman Ben knows he can never have. When Diana is found dead outside her apartment, Ben's infatuation drives him on a hunt to find out what happened to the love of his life. Can Ben find the truth behind Diana's death before someone stops him?